The Role of the Web and Social Media in the Tourism Promotion of a World Heritage Site. The Case of the Alcazar of Seville (Spain) - Foronda-Robles, Concepción; Mondelli, Caterina; Carboni, Donatella (Revista de Estudios Andaluces, 2021)
The Web and the new technologies are useful for guaranteeing the promotion and the tourist enjoyment of a cultural asset. The objective of this study is to analyze the promotional strategy on the official website and on social networks developed by the Alcazar of Seville. With the Facebook´s fall, Instagram and Twitter have gained more importance which have experienced a great growth during 2017, positioning themselves as the social networks that generate the greatest interactions. In the publications, persuasive communication stands out, and details the architectural and landscape attributes of the Real Alcazar of Seville.